2010
DOI: 10.1155/2011/891819
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous and Ethanolic Valeriana officinalis Extracts Change the Binding of Ligands to Glutamate Receptors

Abstract: The effects of two valerian extracts (aqueous and hydroalcoholic) were investigated through [3H]Glutamate ([3H]Glu) and [3H]Fluorowillardine ([3H]FW) receptor binding assays using rat synaptic membranes in presence of different receptor ligands. In addition, the extract stability was monitored spectrophotometrically. Both extracts demonstrated interaction with ionotropic glutamate receptors (iGluRs). However, the extracts displayed considerable differences in receptor selectivity. The hydroalcoholic extract se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…This study, for first time, showed that the effects of valerian and valerenic acid were significantly antagonized in the presence of L-AP3 and EGLU (mGluR antagonists). Our in vivo results clearly demonstrated that Valeriana officinalis and valerenic acid interact with zebrafish group I and II mGluR, confirming our previous in vitro studies [8,9]. Zebrafish are a valuable in vivo biological tool for large screens of phytochemical (natural products) and for studying their physiological response.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This study, for first time, showed that the effects of valerian and valerenic acid were significantly antagonized in the presence of L-AP3 and EGLU (mGluR antagonists). Our in vivo results clearly demonstrated that Valeriana officinalis and valerenic acid interact with zebrafish group I and II mGluR, confirming our previous in vitro studies [8,9]. Zebrafish are a valuable in vivo biological tool for large screens of phytochemical (natural products) and for studying their physiological response.…”
supporting
confidence: 88%
“…Previous research demonstrated that valerian interacts with and modulates GABA receptors [4], is a partial agonist of the 5-HT(5a) receptor [5] and mediates the activation of adenosine receptors [6,7] but the exact mechanism of action of valerian is still unknown. Studies from our lab reveal that valerian extracts also interact with metabotropic glutamate receptors [8,9]. During the past decades, zebrafish have emerged as a useful model species and a powerful bioassay tool in different research areas [10,11].…”
mentioning
confidence: 99%
“…Other studies indicate that VE has antioxidant and neuroprotective effects [6,7,8,9]. Furthermore, VE modulates brain neurotransmitters [10,11,12,13,14], and shows antianxiety, antidepressant, and antiepileptic activity in animal models [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…A variety of therapeutic effects, including hypnotic, sedative, anxiolytic, anticonvulsant, and antidepressant functions, have been determined for valerian (Wagner et al, 1980;Oshima et al, 1995;Andreatini et al, 2002;Del Valle-Mojica et al, 2011;Torres-Hernández et al, 2015). Some studies have tested the effects of valerian only, or in combination with other pharmaceuticals or herbal medicines in treating neurological diseases.…”
Section: Introductionmentioning
confidence: 99%